Pengaruh Mathematical Beliefs dan Self Regulated Learning terhadap Kemampuan Berpikir Kritis Matematis - Najwa Ghafirah Putri; Siska Ryane Muslim; Sri Tirto Madawistama (Media Pendidikan Matematika, 2026)
This study aims to determine the impact of mathematical beliefs and self-regulated learning on mathematical critical thinking skills, both partially and simultaneously. This study uses quantitative research with an associative method. The sample in this study was 42 grade X students at one of the public senior high schools in Tasikmalaya city who were randomly selected using a simple random sampling technique. Data obtained through a questionnaire on mathematical beliefs and self-regulated learning, as well as mathematical critical thinking ability tests, were analyzed using multiple linear regression with the help of IBM SPSS statistics 24 software. The results of the t-test showed that partially mathematical beliefs, self-regulated learning had a positive and significant effect on mathematical critical thinking skills. The results of the F-test showed that mathematical beliefs and self-regulated learning simultaneously had an effect on mathematical critical thinking skills by 32,1%, while 67,9% was influenced by other factors